Gastronomy and hypermediacy - Aksu, Rabia Nur; İnce Karaçeper, Ecem; Keskin, Hilal (Cognizant Communication Corporation, 2024)
This study investigates the evolving role of media in conveying gastronomic experiences, utilizing Bolter and Grusin’s theory of “remediation” as a conceptual framework. Gastronomy, an essential aspect of cultural and social life, is increasingly mediated through advanced technologies such as visual media, virtual reality, and augmented reality. This research aims to understand how these various media types enhance the representation and transmission of gastronomic elements, providing a more immersive and realistic experience for the audience. A comprehensive literature review was conducted to gather the findings of this study. The primary contribution of this research lies in its systematic compilation and organization of developments in the media used to convey gastronomy through the lens of remediation theory. By evaluating media tools like visual media, virtual reality, and augmented reality from a gastro nomic perspective, the study offers valuable insights into the technological transformation of culinary culture. The findings indicate that media related to gastronomy has reached a state of hypermediacy, characterized by a heightened sense of immediacy and realism. This hypermediacy is achieved through the integration of multiple media forms, creating a rich and engaging user experience. For instance, virtual reality allows users to virtually step into a restaurant and interact with the environment, while augmented reality enhances the dining experience by overlaying digital information onto the real world. Moreover, the study highlights the significance of media in democratizing gastronomic knowledge and experiences. High culinary cultures, once accessible only to a select few, are now available to a broader audience through various media platforms. Television programs, social media, and digital applications play a crucial role in popularizing and disseminating culinary traditions, making them an integral part of everyday life. In conclusion, this study underscores the dynamic and transformative nature of media in the field of gastronomy. By providing a detailed analysis of the evolution of media tools and their impact on gastronomic experiences, the research offers new perspectives for future studies.
Keywords: Tourism; Media; Remediation; Immediacy; Bolter and Grusin